2006
DOI: 10.1055/s-2005-865718
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Energy Cost and Sensation Responses During Submaximal Running Exercise - Positive Effects of Wearing Compression Tights

Abstract: This study aimed to examine the effects of wearing compression compared to classic elastic tights and conventional shorts (control trial) on oxygen cost and sensation responses during submaximal running exercise. In part I, aerobic energy cost was evaluated in six trained runners at 10, 12, 14, and 16 km x h(-1). In part II, the increase in energy cost over time (i. e., slow component expressed as difference in VO2 values between min 2 and end-exercise) was determined in six trained runners at a constant runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
141
3
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(154 citation statements)
references
References 26 publications
4
141
3
6
Order By: Relevance
“…But during walks at 4.3 km/h or runs at 10.1 km/h, Murthy et al (21) reported no change in leg intramuscular pressure with elastic leggings (~25 mmHg at the calf). These results seem to indicate that hemodynamic effects could also occur only at very low-intensity walks / runs (17,18,20). Finally Maton et al (17) showed an increase of leg intramuscular pressure with compression socks (~11 mmHg at the calf) at rest but also during isometric and concentric exercises (dorsal flexion of the ankle).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…But during walks at 4.3 km/h or runs at 10.1 km/h, Murthy et al (21) reported no change in leg intramuscular pressure with elastic leggings (~25 mmHg at the calf). These results seem to indicate that hemodynamic effects could also occur only at very low-intensity walks / runs (17,18,20). Finally Maton et al (17) showed an increase of leg intramuscular pressure with compression socks (~11 mmHg at the calf) at rest but also during isometric and concentric exercises (dorsal flexion of the ankle).…”
Section: Introductionmentioning
confidence: 92%
“…These mechanisms are also used by manufacturers to justify the use of compression garments during running and cycling activities. To date though, this statement seems to be more unclear with studies both support- ing (17)(18)(19) and refuting (19)(20)(21) hemodynamics effects during the effort. For example, Boucourt et al examined the changes in tissue oxygen saturation (StO 2 ) with calf compression sleeves (28 mmHg) during an incremental cycling exercise (3 min at each intensity -40, 80, 120, 160 and 200 W) (19).…”
Section: Introductionmentioning
confidence: 98%
“…Some physiological research can explain this phenomenon: one showed that compression garments shortened the time that the muscle needed to reach its optimized temperature (38.5℃) [30]; at the mean time, they prevent the human thermal regulation system from getting over-heated and over-wet [31]. In addition, some studies on post-match recovery proved that compression garments can facilitate the elimination of muscle oxygenation and CK [32], alleviate DOMS [33], decrease the accumulation of the bloodʹs lactic acid [34,35] and, finally, accelerate the recovery process after high intensity exercise [36].…”
Section: Compression Garments and Sports Fatiguementioning
confidence: 99%
“…Leistungssteigernde Effekte im Sinne von einer erhöhten Laufgeschwindigkeit bei der aeroben und anaeroben Schwelle, bei einem Stufentest auf dem Laufband, observierte Kemmler et al (2009) [3]. Ähnliche Ergebnisse präsentierte Bringard et al (2006) bezogen auf einen signifikant niederen aerobe Energieaufwand bei elastischen Kompressionshosen im Vergleich zu normalen Trainingshosen [8].…”
unclassified